Strangulated Femoral Hernia Turned to Be Peritoneal Cyst. (19th November 2012) - Dellaportas, Dionysios; Polymeneas, George; Dastamani, Christina; Kairi-Vasilatou, Evi; Papaconstantinou, Ioannis
Abstract : Introduction . A peritoneal inclusion cyst is a very rare mesenteric cyst of mesothelial origin usually asymptomatic. A rare case of an 82-year-old white Caucasian female with a femoral hernia containing a large peritoneal inclusion cyst, mimicking strangulated hernia, is presented herein. Case Presentation . The patient was admitted to our hospital suffering from a palpable groin mass on the right, which became painful and caused great discomfort for the last hours. Physical examination revealed a tender and tense, irreducible groin mass. An inguinal operative approach was selected and the mass was found protruding through the femoral ring. After careful dissection it turned out to be a large unilocular cyst, containing serous fluid, probably originating from the peritoneum. McVay procedure was used to reapproximate the femoral ring. Histologic examination showed a peritoneal inclusion cyst. Discussion . Peritoneal inclusion cysts are usually asymptomatic but occasionally present with various, nonspecific symptoms according to their size. Our case highlights that high index of clinical suspicion and careful exploration during repair of a hernia is mandatory in order to reach the correct diagnosis about hernia's contents.